Rotating frame MRI relaxations as markers of diffuse white matter abnormalities in multiple sclerosis - Filip, Pavel; Svatkova, Alena; Carpenter, Adam F; Eberly, Lynn E; Nestrasil, Igor; Nissi, Mikko J; Michaeli, Shalom; Mangia, Silvia (NeuroImage. Clinical, 2020)
Even though MRI visualization of white matter lesions is pivotal for the diagnosis and management of multiple sclerosis (MS), the issue of detecting diffuse brain tissue damage beyond the apparent T2-hyperintense lesions continues to spark considerable interest. Motivated by the notion that rotating frame MRI methods are sensitive to slow motional regimes critical for tissue characterization, here we utilized novel imaging protocols of rotating frame MRI on a clinical 3 Tesla platform, including adiabatic longitudinal, T1ρ, and transverse, T2ρ, relaxation methods, and Relaxation Along a Fictitious Field (RAFF) in the rotating frame of rank 4 (RAFF4), in 10 relapsing-remitting multiple sclerosis patients and 10 sex- and age-matched healthy controls. T1ρ, T2ρ and RAFF4 relaxograms extracted from the whole white matter exhibited a significant shift towards longer relaxation time constants in MS patients as compared to controls. T1ρ and RAFF4 detected alterations even when considering only regions of normally appearing white matter (NAWM), while other MRI metrics such as T1w/T2w ratio and diffusion tensor imaging measures failed to find group differences. In addition, RAFF4, T2ρ and, to a lesser extent, T1ρ showed differences in subcortical grey matter structures, mainly hippocampus, whereas no functional changes in this region were detected in resting-state functional MRI metrics. We conclude that rotating frame MRI techniques are exceptionally sensitive methods for the detection of subtle abnormalities not only in NAWM, but also in deep grey matter in MS, where they surpass even highly sensitive measures of functional changes, which are often suggested to precede detectable structural alterations. Such abnormalities are consistent with a wide spectrum of different, but interconnected pathological features of MS, including the loss of neuronal cells and their axons, decreased levels of myelin even in NAWM, and altered iron content.
Keywords: dospělí; interpretace obrazu počítačem; Magnetic Resonance Imaging; Female; Adult; Image Interpretation, Computer-Assisted; ženské pohlaví; průřezové studie; White Matter; relabující-remitující roztroušená skleróza; neurozobrazování; lidé; magnetická rezonanční tomografie; mozek; Cross-Sectional Studies; Male; Brain; Multiple Sclerosis, Relapsing-Remitting; lidé středního věku; mužské pohlaví; Middle Aged; Neuroimaging; bílá hmota; Humans